Convalescent plasma for the treatment of patients with severe coronavirus disease 2019: A preliminary report. Issue 3 (5th October 2020) - Omrani, Ali S.; Zaqout, Ahmed; Baiou, Anas; Daghfal, Joanne; Elkum, Naser; Alattar, Rand A.; Bakdach, Dana; Abusriwil, Hatem; Mostafa, Abdalrahman M.; Alhariri, Bassem; Ambra, Naseem; Khatib, Mohamed; et al.
Abstract: Background: The role of convalescent plasma therapy for patients with coronavirus disease 2019 (COVID‐19) is unclear. Methods: We retrospectively compared outcomes in a cohort of critical COVID‐19 patients who received standard care (SC Group) and those who, in addition, received convalescent plasma (CP Group). Results: In total, 40 patients were included in each group. The median patient age was 53.5 years (interquartile range [IQR] 42–60.5), and the majority of patients required invasive ventilation (69, 86.2%). Plasma was harvested from donors after a median of 37 days (IQR 31–46) from the first positive severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) polymerase chain reaction (PCR) result and 26 days (IQR 21–32) after documented viral clearance; it was administered after a median of 10 days (IQR 9–10) from the onset of symptoms and 2.5 days (IQR 2–4) from admission to intensive care unit. The primary endpoint of improvement in respiratory support status within 28 days was achieved in 26 patients (65%) in the SC Group and 31 patients (77.5%) in the CP Group ( p = .32). The 28‐day all‐cause mortality (12.5% vs. 2.5%; p = .22) and viral clearance (65% vs. 55%; p = .49) were not significantly different between the two groups. Convalescent plasma was not significantly associated with the primary endpoint (adjusted hazard ratio 0.87; 95% confidence interval 0.51–1.49; p = .62). Adverse events were balanced between the two study groups. Conclusion: In severe COVID‐19, convalescent plasma therapy was not associated with clinical benefits. Randomized trials are required to confirm our findings. Highlights: In patients with severe influenza, convalescent plasma was associated with improved viral clearance and reduced mortality. In this retrospective observational study of patients with severe COVID‐19, convalescent plasma was not associated with improvement in respiratory support status within 28 days, all‐cause mortality, or viral clearance. Randomized trials are urgently required to confirm these findings.